2013
DOI: 10.1016/j.jval.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Boceprevir in Patients Previously Treated for Chronic Hepatitis C Genotype 1 Infection in the United States

Abstract: Objectives The phase 3 trial, RESPOND-2, demonstrated that the addition of boceprevir (BOC) to peginterferon-ribavirin (PR) resulted in significantly higher rates of sustained virologic response (SVR) in previously treated patients with chronic hepatitis C virus (HCV) genotype-1 infection as compared with PR alone. We evaluated the cost-effectiveness of treatment with boceprevir in previously treated chronic hepatitis C patients in the United States utilizing treatment related data from RESPOND-2 and PROVIDE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…We used a weekly cycle length to advance time in the model. The structure of the model was based on our previously published and validated Markov cohort model (22, 23). …”
Section: Methodsmentioning
confidence: 99%
“…We used a weekly cycle length to advance time in the model. The structure of the model was based on our previously published and validated Markov cohort model (22, 23). …”
Section: Methodsmentioning
confidence: 99%
“…There are different rules of thumb to classify incremental cost per QALY ratios. We employed a widely used [15,16,17,18] threshold of 50,000 USD PPP per QALY or DALY to distinguish cost-effective from economically unfavourable interventions. If the test intervention is less costly and more effective than the control intervention, the test intervention is called ‘dominant'.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar study of the cost-effectiveness of boceprevir in previously treated individuals, boceprevir was also found to be cost-effective. 36 Blázquez-Pérez et al 37 investigated the costeffectiveness of combination therapy with a newly developed protease inhibitor (boceprevir or telaprevir) plus PEG þ RBV versus SOC in treatment-naive patients with G1 HCV according to data obtained from clinical trials. The data showed that both protease inhibitors appeared cost-effective compared with SOC, with boceprevir producing slightly more favorable ICER and QALY values in treatment-naïve individuals.…”
Section: Discussionmentioning
confidence: 99%